1995
DOI: 10.1084/jem.181.6.2085
|View full text |Cite
|
Sign up to set email alerts
|

Low HLA-C expression at cell surfaces correlates with increased turnover of heavy chain mRNA.

Abstract: SummaryIn comparison with HLA-A and -B, the protein products of the HLA-C locus are poorly characterized, in part because of their low level of expression at the cell surface. Here, we examine how protein-protein interactions during assembly and regulation of the mRNA level affect cell surface expression of HLA-C. We find that intrinsic properties of the HLA-C heavy chain proteins do not correlate with low cell surface expression: HLA-C heavy chains associate and dissociate with fl2-microglobulin (fl2m) at rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 48 publications
4
116
0
Order By: Relevance
“…In contrast, McCutcheon et al (10) did not find evidence for impaired assembly of HLA-Cw3, -Cw6, and -Cw7 complexes and found that assembled HLA-A2, -B27, and -Cw1 complexes are equally long-lived. Taking advantage of the distribution of the L31 epitope on a set of alleles that includes one member from each of the eight serologically defined HLA-C specificities and five HLA-B alleles, we have been able to carry out a homogeneous comparison of the accumulation of the different unfolded heavy chains and to estimate their assembly abilities.…”
Section: An Abundant Pool Of Free Hla-c Heavy Chain Conformers In B Lmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, McCutcheon et al (10) did not find evidence for impaired assembly of HLA-Cw3, -Cw6, and -Cw7 complexes and found that assembled HLA-A2, -B27, and -Cw1 complexes are equally long-lived. Taking advantage of the distribution of the L31 epitope on a set of alleles that includes one member from each of the eight serologically defined HLA-C specificities and five HLA-B alleles, we have been able to carry out a homogeneous comparison of the accumulation of the different unfolded heavy chains and to estimate their assembly abilities.…”
Section: An Abundant Pool Of Free Hla-c Heavy Chain Conformers In B Lmentioning
confidence: 89%
“…Also in contrast to HLA-A and HLA-B, HLA-C is a rather poor assembler. This latter feature has been proposed to correlate with impaired intracellular transport and low surface expression (8,9), although this conclusion has been questioned (10).…”
mentioning
confidence: 97%
“…In all, 24 patients (21%), however, were mismatched for HLA-C only (Table 1), which allowed the analysis of the significance of this locus which is expressed at lower levels than other class I antigens. 21 The 79 HLA allele-mismatches were distributed as follows: five HLA-A (two single mismatches), 13 HLA-B (6), 36 HLA-C (24), seven DRB1 (4), seven DRB3 (4) and 11 DQB1 (2). No DRB5 incompatibility was detected.…”
Section: Hlamentioning
confidence: 99%
“…HLA-C molecules are expressed at a low level on the cell surface compared with HLA-A and -B (1)(2)(3)(4)(5), owing in part to the poor assembly of HLA-C heavy chains with β2 microglobulin (2,4) and the retention of HLA-C molecules in the endoplasmic reticulum, where they are partially degraded (3). An internalization and lysosomal targeting signal in the cytoplasmic tail of HLA-C further regulates its surface expression (6).…”
mentioning
confidence: 99%